How Entrepreneurial Leaders Can Navigate a Crisis Successfully: Lessons and Hypotheses - Flamholtz, Eric; Randle, Yvonne (Senate Hall, 2021)
This article deals with leadership responses to organizational crises. A sample of organizations were examined in order to derive insights and lessons which might help corporate leaders navigate organizational crises, including: American Express, Chrysler, Disney, Eastman Kodak, International Harvester/Navistar, Osborne Computer, Sears, United Airlines, and Westfield. The sample included successful and unsuccessful crisis responses, entrepreneurial and established institutional enterprises, and crises precipitated by external factors and/or internal factors. The study addresses the nature of the crises encountered, the underlying causes, whether there are significant differences between entrepreneurial companies and established companies, and whether a set of organizational preconditions of susceptibility to a crisis exists. It also identifies lessons to be derived from both successful and unsuccessful leadership of a crisis, and areas for future research.
Keywords: organizational crisis|crisis susceptibility|successful and unsuccessful crisis leadership